2005
DOI: 10.1176/jnp.17.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia, Depression, and Motor Functioning in Parkinson’s Disease During Treatment With Pramipexole

Abstract: Anhedonia, a core symptom of depression, correlates with motor alterations in major depressive disorder and has been assumed to be frequent in depressed patients with Parkinson's disease (PD). In the present study, the authors assessed for the first time frequency of anhedonia in patients with idiopathic Parkinson's disease (N = 657) and the relationship of anhedonia and parkinsonian motor deficits during treatment with pramipexole. Mild depression was present in 47% of the patients and moderate to severe depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(45 citation statements)
references
References 20 publications
1
40
1
3
Order By: Relevance
“…A randomized, open-label comparative trial reported a significant decrease in Zung depression score after eight months of either pramipexole or pergolide; improvement on the Montgomery-Åsberg Depression Rating Scale was seen only among the pramipexole recipients [19]. Another, observational study involving 657 PD outpatients found that pramipexole improved anhedonia, as evaluated by the Snaith-Hamilton Pleasure Scale [14]. Both studies included PD patients with motor complications such as fluctuations and dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A randomized, open-label comparative trial reported a significant decrease in Zung depression score after eight months of either pramipexole or pergolide; improvement on the Montgomery-Åsberg Depression Rating Scale was seen only among the pramipexole recipients [19]. Another, observational study involving 657 PD outpatients found that pramipexole improved anhedonia, as evaluated by the Snaith-Hamilton Pleasure Scale [14]. Both studies included PD patients with motor complications such as fluctuations and dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…Both agonists exhibited an antidepressant effect, as measured by the Zung self-rating depression scale, but only pramipexole showed a significant decrease in the average score on the Montgomery-Åsberg Depression Rating Scale. In another study, a prospective observational trial in 657 PD outpatients, pramipexole significantly reduced anhedonia, a core symptom of depression [14].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Two controlled studies published recently show antidepressant properties of pramipexole in patients with bipolar II depression. Antidepressive effects of pramipexole have been confirmed in large populations of PD patients during clinical routine using open study designs [5,9]. There is a lack of controlled studies to show the specific effect on depression in PD patients.…”
Section: ■ Dopamine Agonistsmentioning
confidence: 99%
“…Depression is one of the common complications in Parkinson's disease (Yamamoto 2001), and decreased dopamine transmission has been suggested as one of the causes of this phenomenon (Lemke 2008). Indeed, dopamine receptor agonists such as pramipexole and pergolide demonstrated their effectiveness both on depression and motor functioning in patients with Parkinson's disease (Rektorová et al 2003;Lemke et al 2005Lemke et al , 2006Leentjens et al 2009). Patients with treatment-resistant depression were also subjected to administration of dopamine receptor agonist in addition to contemporary antidepressants, and favorable results were reported with regard to pramipexole (Lattanzi et al 2002), bromocriptine (Inoue et al 1996), and pergolide (Izumi et al 2000).…”
Section: Introductionmentioning
confidence: 99%